1991
DOI: 10.3109/02713689109020329
|View full text |Cite
|
Sign up to set email alerts
|

Ocular absorption and distribution of loteprednol etabonate, a soft steroid, in rabbit eyes

Abstract: Loteprednol etabonate (LE) is a "soft" steroid belonging to a unique class of glucocorticoids. LE possesses a metabolically labile 17 beta-chloromethyl ester function which was designed in order to be hydrolyzed to an inactive carboxylic acid moiety. The ocular absorption and metabolism of a 14C-labelled LE was evaluated in New-Zealand White rabbits after administration of a 0.5% suspension in both eyes. At various time points following ocular administration, the cornea, aqueous humor, and iris-ciliary body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 6 publications
5
57
0
Order By: Relevance
“…The cornea also showed the highest ratio of metabolite to Loteprednol Etabonate (41), indicating that the cornea was the prime site of metabolism, while aqueous humour concentrations of LE were nearly 100-fold lower. This finding suggested that Loteprednol Etabonate may exert a decreased IOP effect as compared to other glucocorticoids [78]. Further a comparison of the IOP-elevating activity of Loteprednol Etabonate with that of Dexamethasone (2) in rabbits confirmed a lack of IOP effect with LE [79,80].…”
Section: Loteprednol Etabonate (41) and Its Clinical Investigations Isupporting
confidence: 53%
See 1 more Smart Citation
“…The cornea also showed the highest ratio of metabolite to Loteprednol Etabonate (41), indicating that the cornea was the prime site of metabolism, while aqueous humour concentrations of LE were nearly 100-fold lower. This finding suggested that Loteprednol Etabonate may exert a decreased IOP effect as compared to other glucocorticoids [78]. Further a comparison of the IOP-elevating activity of Loteprednol Etabonate with that of Dexamethasone (2) in rabbits confirmed a lack of IOP effect with LE [79,80].…”
Section: Loteprednol Etabonate (41) and Its Clinical Investigations Isupporting
confidence: 53%
“…Loteprednol Etabonate (LE) is predictably metabolized by local esterases into its inactive metabolite Δ 1 -cortienic acid (40) which has been confirmed through animal studies [20]. Clinical studies by Druzgala et al [78] have confirmed that the highest concentration of LE was found in cornea, followed by the iris/ciliary body and aqueous humour. The cornea also showed the highest ratio of metabolite to Loteprednol Etabonate (41), indicating that the cornea was the prime site of metabolism, while aqueous humour concentrations of LE were nearly 100-fold lower.…”
Section: Loteprednol Etabonate (41) and Its Clinical Investigations Imentioning
confidence: 59%
“…35,36 Previous studies have confirmed the relatively lower risk of IOP elevation with LE compared with other ocular steroids, including studies in known steroid responders. [37][38][39][40][41][42][43][44][45] Limitations of this analysis included the lack of either a non-active control, or a control of a different drug category and the 2-week follow-up period.…”
Section: Discussionmentioning
confidence: 94%
“…LE (41) was selected for development based on various considerations including the TI, availability, synthesis, and "softness" (the rate and easiness of metabolic deactivation). Early studies in rabbits [164,167] and rats [168] demonstrated that, consistent with its design, 41 is indeed active, is metabolized into its predicted metabolites (42,43) (Fig. 12), and these metabolites are inactive [163].…”
Section: Softmentioning
confidence: 99%
“…A number of them maintained high binding affinity at the benzodiazepine receptor (<50 nM), showed good (>100-fold) separation of activity between the (active) ester and the (inactive) acid, and were able to cause loss of the righting reflex (LRR) in rats, an effect associated with benzodiazepine full agonism. Structures such as CNS 7259X (164) [367,369] and CNS 7056 (166) [368,370] (Fig. 37) were selected for development, which has been taken over by CeNeS and later PAION.…”
Section: Soft Benzodiazepine Analogsmentioning
confidence: 99%